Conceptualising talent in multinational hotel corporations. Issue 10 (14th October 2019) - Jooss, Stefan; McDonnell, Anthony; Burbach, Ralf; Vaiman, Vlad
Abstract : Purpose: To identify, develop and retain talent, an important first step is to ensure that key stakeholders in the talent management (TM) process have a shared view of what is meant by talent within the organisation. The purpose of this paper is to conceptualise how talent is defined in the context of the hospitality industry and to examine the degree of (mis)alignment among corporate and business unit leaders. Design/methodology/approach: The paper uses a qualitative approach consisting of 73 interviews with stakeholders at corporate and business unit levels in three multinational hotel corporations. In addition, documents were collected and analysed to support the interview data. Findings: Each organisation had a formal approach to conceptualising talent at a corporate level. Both inclusive and exclusive views on talent as well as a broad set of characteristics that make up talent were reported with the importance of organisational values being prominent. However, despite formal global policies being in place, considerable divergence in practice was found across organisational levels. Practical implications: A lack of clarity on what talent means in an organisational setting may lead to an inconsistent talent identification process which may lead to negative perceptions of fairness among employees. This may, in turn, bring about disgruntled employees and increased turnover. Originality/value: This paper provides empirical evidence to the limited body of knowledge on the conceptualisation of talent. The display of organisational values emerged as important to being labelled talent, a factor that has received scant consideration in the literature.